Propositional and non- propositional functions of /Keda/ in the language of Egyptian film - Hussein, Mona (AUC Knowledge Fountain, 2016)
This thesis explores the pragmatic and syntactic functions of the word /keda/ within a propositional and non-propositonal meaning. It also investigates /keda/within the sentence structure as a propositional meaning and outside the sentence structure as a non-propositional meaning. The analysis of /keda/ is done using a corpus of Egyptian Colloquial Arabic movies. The study uses Wordsmith Tools software to show and analyze the data./Keda/ has different meanings within the sentence structure like ‘this’/’that’, ‘so, ‘in this way’ and other meanings. It has different pragmatic and syntactic functions. When/keda/ is outside the sentence structure, it acts like the discourse markers just, like, sort of or kind of. The findings allow both teachers to better understand and use the word /keda/.